The Influence of Idealism and Relativism Ethical Orientations on Whistleblowing with Ethical Sensitivity as a Moderating Variable - Syamsuddin, Sofyan; Riyanti, Riyanti; Sundari, Sri; Kartini, Kartini (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of idealism and relativism ethical orientations on whistleblowing behavior, as well as to examine the role of ethical sensitivity as a moderating variable in auditors at the Inspectorate throughout Luwu Raya. The research method used is quantitative with a causality approach, using data from questionnaires distributed to 102 auditors who have carried out at least one audit task. Data analysis was carried out using validity tests, multiple linear regression, and moderation tests using SPSS 30. The results showed that idealism ethical orientation had no significant effect on whistleblowing behavior, while relativism ethical orientation had a significant effect. Ethical sensitivity was proven to strengthen the influence of both idealism and relativism ethical orientations on whistleblowing behavior. This finding emphasizes the importance of ethical sensitivity in increasing auditors' tendency to whistleblow, both in idealism and relativism oriented auditors. This study provides implications for the Inspectorate in formulating policies to strengthen ethics and an effective whistleblowing system to support clean and accountable governance.